2020
DOI: 10.5765/jkacap.190036
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Status in Children with Attention-Deficit/Hyperactivity Disorder and/or Autism Spectrum Disorder

Abstract: The objective of this study was to assess serum, hair, and urinary magnesium (Mg) levels in children with attention-deficit/ hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and both ASD and ADHD to reveal potential interactive effects. Methods: A total of 148 boys aged 4-9 years old were enrolled in this study, including 44 children with ADHD, 40 pediatric patients with ASD, 32 patients with both ADHD and ASD, as well as 32 healthy neurotypical children. Hair, serum, and urinary Mg levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…For instance, Skalny et al demonstrated that the Mg concentration in the hair (17.91 μg/g for ASD children versus 18.84 μg/g for TD children) and urine (108.59 μg/mL for ASD children versus 118.51 μg/mL for TD children) of ASD children was lower than the unmatched TD control. However, the findings were non-significant [ 138 ]. Priya et al demonstrated that the Mg concentrations in hair of low functioning autism (LFA) (mean 174.02 ± 20.88 μg/g), medium functioning autism (MFA) (mean 202.21± 24.26 μg/g) and high functioning autism (HFA) (mean 236.31 ± 28.35 μg/g) children were significantly lower than the control group (mean 454.36 ± 54.52 μg/g).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Skalny et al demonstrated that the Mg concentration in the hair (17.91 μg/g for ASD children versus 18.84 μg/g for TD children) and urine (108.59 μg/mL for ASD children versus 118.51 μg/mL for TD children) of ASD children was lower than the unmatched TD control. However, the findings were non-significant [ 138 ]. Priya et al demonstrated that the Mg concentrations in hair of low functioning autism (LFA) (mean 174.02 ± 20.88 μg/g), medium functioning autism (MFA) (mean 202.21± 24.26 μg/g) and high functioning autism (HFA) (mean 236.31 ± 28.35 μg/g) children were significantly lower than the control group (mean 454.36 ± 54.52 μg/g).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there was a study linking low iodine levels in the first trimester of pregnancy and processing disorders of the child including children with ASD [61]. Additional deficiencies in iron [62], magnesium [63] and vitamins A and D [64] are often seen to exacerbate symptoms in children with ASD. It is therefore worth noting that speaking with experts may benefit parents to create more awareness.…”
Section: Theme 5: Parents' Perception Of Child Nutritional Statusmentioning
confidence: 99%
“…One study showed that serum magnesium levels in people with ADHD were significantly lower than in the general population as well as in laboratory references. Therefore, given the role of magnesium in the nervous system, it is likely that magnesium supplementation within this patient population can help improve symptoms [ 42 , 43 ]. Similarly, magnesium supplementation has shown to improve several mental health parameters.…”
Section: Discussionmentioning
confidence: 99%